Can ischemia modified albumin (IMA) and total sulfhydryl level (TSH) be used as a biomarker in the diagnosis of bladder tumor? A prospective case-control study - Eryılmaz, Recep; Demir, Canan; Aslan, Rahmi; Demir, Halit; Taken, Kerem (Journal of Surgery and Medicine, 2020)
Aim: Bladder tumor is one of the most common cancers. Cystoscopy, which is an invasive procedure, is used in its diagnosis. We conducted a study to determine whether a more non-invasive method can be used for this purpose. In this study, the uses of Ischemia Modified Albumin (IMA) and total sulfhydryl level (TSH), which are both antioxidant markers, were investigated for the diagnosis of bladder tumor. Methods: Ischemia Modified Albumin (IMA) and total sulfhydryl level (TSH) were identified by the spectrophotometric method. Patients with primary bladder tumors who did not receive any prior treatments or undergo any interventions were included in this prospective case control study. Those with severe cardiac and neurological diseases, other malignancies, acute and chronic infectious diseases, active organ failure, chronic obstructive pulmonary diseases, and other ischemic immunosuppressive diseases, along with individuals with severely low or high serum albumin levels (<20 or >55 g/L) were excluded from the study. Results: Forty-two primary bladder tumors and 45 healthy volunteers were included in the study. Serum IMA and TSH levels of the patient and control groups were compared. Patients with bladder tumors had high serum IMA (P=0.045) levels and low TSH levels (P=0.033). Conclusion: Both IMA and total TSH can be considered non-invasive biomarkers in the diagnosis of bladder tumor. Since there are few studies on this subject in the literature, further, larger studies are needed.